2009
DOI: 10.3748/wjg.15.5722
|View full text |Cite
|
Sign up to set email alerts
|

Gastric dysplasia may be an independent risk factor of anadvanced colorectal neoplasm

Abstract: AIM:To evaluate the relationship between gastric dysplasia and Helicobacter pylori (H pylori ) and the occurrence of colorectal adenoma, and to define the necessity for colonoscopy in patients with gastric dysplasia or H pylori infection. May 2005 to February 2008, 133 patients with established gastric dysplasia by gastroduo denoscopy (EGD) were additionally investigated by colonoscopy. The authors compared results with those of 213 subjects who underwent both EGD and colonoscopy during the same period at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…One additional article was included from the reference review [25]. Finally, 27 articles published from December 1991 to June 2012 were used in the meta-analysis [3,4,[8][9][10]13,14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. These studies included a total of 3792 cases of CRA and 3488 cases of CRC.…”
Section: Resultsmentioning
confidence: 99%
“…One additional article was included from the reference review [25]. Finally, 27 articles published from December 1991 to June 2012 were used in the meta-analysis [3,4,[8][9][10]13,14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. These studies included a total of 3792 cases of CRA and 3488 cases of CRC.…”
Section: Resultsmentioning
confidence: 99%
“…[14] 2009 Korea 73 60 131 82 Serological Inoue et.al. [5] 2011 Japan 201 38 368 110 13 C UBT Hong et.al.…”
Section: Sub-group Analysismentioning
confidence: 97%
“…In patients with GC, CRC is one of the most common synchronous cancers. 9,10 Recently, pre-operative colonoscopy has been recommended for patients with gastric adenocarcinoma. [16][17][18] In addition, a recent retrospective study performed at a single healthcare centre suggested that adenomas of stomach and colorectum may be similar in terms of pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Notably, colorectal cancer (CRC) is one of the most frequent synchronous cancers among patients with primary GC. 9,10 Thus, a synchronous colorectal neoplasm (CRN) should be screened for and eliminated, for example by colonoscopic examination, during pre-operative workup in selected high-risk patients. 11 Furthermore, it was suggested in recent studies, corrected for age and gender, that colonoscopy can be conducted before or after GC surgery because of the high-risk concurrent colon cancer.…”
Section: Introductionmentioning
confidence: 99%